Existence criteria for integral equations in banach spaces. Issue 1 (2001) - O'Regan, Donal; Precup, Radu
Abstract : A Carathéodory existence theory for nonlinear Volterra and Urysohn integral equations in Banach spaces is presented using a Mönch type approach.